2012
DOI: 10.1159/000343656
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Chemotherapy: The Role of p53

Abstract: Background: Hepatocellular carcinoma (HCC) is the most common primary neoplasm of the liver. A major proportion of HCCs also present mutation of the gene that encodes p53, which confers chemoresistance. The main goal of this work is to investigate the effect of cisplatin, doxorubicin and 5-fluoruracil (5-FU) in three human HCC cell lines which differ in p53 expression. Methods: HepG2 (expressing normal p53), HuH7 (expressing mutated p53) and Hep3B2.1-7 (not expressing p53) cell lines were cultivated in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…It is well-known that the transcription of the p21 gene is positively regulated by wild-type p53 protein (35). Given that HepG2 (wild-type p53) and Huh7 (mutant p53) cells hold different statuses of the p53 gene, the p53 mutation in Huh7 cells may contribute to the low level of p21 expression (36). Although deciphering the exact effects of p53 on the expression of p21 is out of the scope of this study, it is clear that induction of p21 by SLC13A5 silencing may contribute to the observed cell cycle arrest in HepG2 but not in Huh7 cells.…”
Section: Slc13a5 Suppression Inhibits Hepatoma Cell Proliferationmentioning
confidence: 99%
“…It is well-known that the transcription of the p21 gene is positively regulated by wild-type p53 protein (35). Given that HepG2 (wild-type p53) and Huh7 (mutant p53) cells hold different statuses of the p53 gene, the p53 mutation in Huh7 cells may contribute to the low level of p21 expression (36). Although deciphering the exact effects of p53 on the expression of p21 is out of the scope of this study, it is clear that induction of p21 by SLC13A5 silencing may contribute to the observed cell cycle arrest in HepG2 but not in Huh7 cells.…”
Section: Slc13a5 Suppression Inhibits Hepatoma Cell Proliferationmentioning
confidence: 99%
“…HCC develops in a complex and progressive process, due to several genetic and epigenetic modifications, in a rich oxidative stress environment [15,16]. These modifications induce autonomous cellular growth and consequent cell cycle deregulation, as well as several mutations in key proteins, such as P53, P21 and β-catenin [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative therapies include chemotherapy and radiotherapy. However, due to the chemoresistant and radioresistant HCC profile, these therapies often fail and are only applied in order to improve the patient's quality of life [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This happens because there are differences in the response to these therapies due, at least in part, to the heterogeneity in expression of genes linked to chemoresistance and radioresistance, where the tumor suppressor gene p53 has a very important role. 5,6 Thus, it is important to find diagnostic tools to identify these genetic differences in order to develop more personalized therapies and increase the therapeutic success.…”
mentioning
confidence: 99%